Предмет психологии,как основа психолого-педагогической деятельности - Филиппова, Вера; Тарасов, Андрей (Զանգակ հրատ.)
Defining the discipline of psychology is still an important issue. Scientific analysis of psychological literature on the problem of determining the subject matter of psychology has shown the ambiguity of the term which is typical for psychological knowledge. Understanding the term “subject matter of psychology” is different depending on the numerous options of explicit and implicit context used by different authors as they adjoin “existing”, “objective reality”, “object”, “subject”, “knowledge”, “method”, and other terms. The article includes the review of the term “the subject of psychology” defined in the works of Russian and foreign scholars. It is stated that the development of views on the subject of psychology has not stopped at the moment. It is concluded that the predecessors have contributed greatly to understanding the subject field of psychology. The morphological analysis of scientific definitions “the object of psychology” has been carried out. The usage frequency of the words defining the scientific content of the subject matter of psychology has been analyzed. Հոդվածում հեղինակների կողմից «հոգեբանության առարկան » հասկացությունն ու բովանդակությունը բնորոշվում են իբևր արդիական հիմնախնդիր: Հեղինակների կողմից նշյալ հիմնախնդրի բնորոշմանը նվիրված հոգեբանամանկավարժական գիտական գրականության վերլուծությունը վերհանեց հասկացության բազմաբովանդակությունը, ինչպես նաև այն, որ «Հոգեբանության առարկան » եզրույթը տարաընկալման տեղիք է տալիս՝ կապված նրա կիրառման ակնառու և ոչ ակնառու բազմաթիվ տարբերակներից, որոնք կիրառվել են տարբեր հեղինակների կողմից, նրան հարակից այնպիսի եզրույթների կիրառմամբ, ինչպիսիք են «ռեալություն, », «օբյեկտ»,«սուբյեկտ», «գիտելիք », «մեթոդ », «իմացություն », «գիտություն » և այլն: Հոդվածում ներկայացված են հոգեբանության առարկայի թե՛ նախկին խորհրդային միության, և թե՛ արտասահմանյան գիտնականների բնորոշումները:
Keywords: Психология